[Et3NH][HSO4] catalyzed efficient synthesis of 5-arylidene-rhodanine conjugates and their antitubercular activity - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Research on Chemical Intermediates, 2016)
We have described a highly efficient, safer protocol for the synthesis of 5-arylidene-rhodanine conjugates catalyzed by Bronsted acidic ionic liquid [Et3NH][HSO4] in excellent yields. The protocol offers cost-effective, environmentally benign, solvent-free conditions and recycle-reuse of the catalyst. The synthesized 5-arylidene-rhodanine conjugates were characterized on the basis of (1) H NMR, C-13 NMR and HRMS spectral data. A series of 5-arylidene-rhodanine derivatives 3a-h, 4a-h were synthesized and evaluated for their in vitro antitubercular activity against dormant Mycobacterium tuberculosis H37Ra and M. bovis BCG strains. Moreover, compounds 3a, 3b, 3e, 3f, 3g, 3h and 4f exhibited good antitubercular activity and were also evaluated for anti-proliferative activity against MCF-7, A549 and HCT116 cell lines using modified MTT assay and found to be noncytotoxic. Compounds 3a-h and 4f were further screened for their antibacterial activity against four bacteria strains to assess their selectivity towards M. tuberculosis. Furthermore, in silico ADME prediction of all the tested compounds followed the criteria for orally active drug and, therefore, these compounds may have a good potential for eventual development as oral agents.

Facile synthesis of 1,3-thiazolidin-4-ones as antitubercular agents - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Arkile, Manisha A.; Yeware, Amar; Sarkar, Dhiman; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
We have developed, highly efficient, one-pot, solvent-free, [Et3NH][HSO4] catalyzed multicomponent reaction protocol for the synthesis of 1,3-thiazolidin-4-ones in excellent yields. For the first time, the 1,3-thiazolidin-4-ones were evaluated in vitro for their antimycobacterial activity against Mycobacterium tuberculosis dormant MTB H37Ra and Mycobacterium bovis BCG strains. Among the synthesized basic 1,3-thiazolidin-4-ones, particularly the compounds 4c, 4d, 4e, 4f, 4h, 4i and 4j displays promising antitubercular activity along with no significant cytotoxicity against the cell lines MCF-7, A549 and HCT-116. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular; Cytotoxicity; Green protocol; Multicomponent reaction

Novel tetrazoloquinoline-rhodanine conjugates: highly efficient synthesis and biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nawale, Laxman; Yeware, Amar; Sarkar, Dhiman; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Shingate, Bapurao B. (Bioorganic & Medicinal Chemistry Letters, 2016)
In search of new active molecules against Mycobacterium tuberculosis (MTB) H37Ra and Mycobacterium bovis BCG, a small focused library of rhodanine incorporated tetrazoloquinoline has been efficiently synthesized by using [HDBU][HSO4] acidic ionic liquid. The compound 3c found to be promising inhibitor of MTB H37Ra and M. bovis BCG characterized by lower MIC values 4.5 and 2.0 mu g/mL, respectively. The active compounds were further tested for cytotoxicity against HeLa, THP-1, A549 and PANC-1 cell lines using MTT assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Again, the synthesized compounds were found to have potential antifungal activity. Furthermore, to rationalize the observed biological activity data, the molecular docking study also been carried out against a potential target Zmp1 enzyme of MTB H37Ra, which revealed a significant correlation between the binding score and biological activity for these compounds. The results of in vitro and in silico study suggest that these compounds possess ideal structural requirement for the further development of novel therapeutic agents. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Antitubercular; Cytotoxicity; Docking study; Rhodanine derivatives

Novel red fluorescence protein based microplate assay for drug screening against dormant mycobacterium tuberculosis by using paraffin - Yeware, Amar; Sarkar, Dhiman (Tuberculosis, 2018)
The hypoxia model of dormancy is widely used in drug screening programs to identify novel inhibitors against latent Mycobacterium tuberculosis disease. In earlier reported microplate assays, hypoxia was maintained by either sealing the microplate or shifting in an anaerobic chamber to develop dormant phenotype. In these assays, inhibitors were added during inoculation, which mainly represents the active stage inhibitors instead of the dormant ones. Herein, the culture was covered with paraffin to develop hypoxia condition and consequently providing the advantage of adding compounds at any stage during incubation of 96-well plate. The stable expression of the red fluorescent protein in the bacilli under both actively growing as well as dormant conditions also facilitate the reliable estimation of growth and inhibition kinetics of bacilli in medium. Furthermore, S/N ratio and Z' factor of this assay were found to be > 27 and 0.91-0.94 respectively, which confirm the robustness of the protocol. This newly developed drug-screening assay offers an easy, inexpensive, safe and high throughput-screening tool to search novel antitubercular inhibitors against both active and dormant bacilli. The red fluorescent H37Ra strain is a suitable surrogate for the more virulent H37Rv strain, and thus this effort will help in combating latent tuberculosis.

High content screening assay for identifying inhibitors against active and dormant state intracellular Mycobacterium tuberculosis - Yeware, Amar; Agrawal, Sonia; Sarkar, Dhiman (Journal of Microbiological Methods, 2019)
The antitubercular drug development pipeline could start with an in vitro investigation of several compounds to examine their effect on active and dormant state Mycobacterium tuberculosis (Mtb). However, in vitro screening of dormant state bacilli cannot provide enough information on the simultaneous effect of a compound on the host. Therefore, we developed a live cell fluorescence based screening protocol by utilizing the high content system for determining the effect of inhibitors against active and dormant state intracellular mycobacteria. THP-1 macrophages infected with an actively growing and hypoxia derived dormant Mtb culture were standardized to develop the screening protocol. The signal to noise ratio and the Z' factor of this assay were found to be 7.5-29 and 0.6-0.8, respectively, which confirm the robustness of the protocol. The protocol was then validated with standard inhibitors. This newly developed drug screening assay offers an easy, safe, image based high content screening tool to search for novel antitubercular inhibitors against both active and dormant state intracellular mycobacteria. Therefore, this assay could fill in the gap between in vitro and in vivo latent tuberculosis drug screening programs.

Using diphenyleneiodonium to induce a viable but non-culturable phenotype in Mycobacterium tuberculosis and its metabolomics analysis - Yeware, Amar; Gample, Suwarna; Agrawal, Sonia; Sarkar, Dhiman (Plos One, 2019)
Depletion of oxygen levels is a well-accepted model for induction of non-replicating, persistent states in mycobacteria. Increasing the stress levels in mycobacterium bacilli facilitates their entry into a non-cultivable, dormant state. In this study, it was shown that diphenyleneiodonium, an inhibitor of NADH oxidase, induced a viable, but non-culturable state in mycobacteria, having similar features to dormant bacilli, like loss of acid-fastness, upregulation of stress-regulated genes and decreased superoxide levels as compared to actively growing bacilli. Comprehensive, untargeted metabolic profiling also confirmed a decrease in biogenesis of amino acids, NAD, unsaturated fatty acids and nucleotides. Additionally, an increase in the level of lactate, fumarate, succinate and pentose phosphate pathways along with increased mycothiol and sulfate metabolites, similar to dormant bacilli, was observed in the granuloma. These non-cultivable bacilli were resuscitated by supplementation of fetal bovine serum, regaining their culturability in liquid as well as on agar medium. This study focused on the effect of diphenyleneiodonium treatment in causing mycobacteria to rapidly transition from an active state into a viable, but non-cultivable state, and comparing their characteristics with dormant phenotypes.

In silico studies, synthesis and antitubercular activity of some novel quinoline - azitidinone derivatives - Chitre, Trupti S.; Asgaonkar, Kalyani D.; Vikhe, Amrut B.; Patil, Shital M.; Garud, Dinesh R.; Khedkar, Vijay M.; Sarkar, Dhiman; Nawale, Laxman U.; Yeware, Amar (Current Computer-Aided Drug Design, 2021)
Background: Diarylquinolines like Bedaquiline have shown promising antitubercular activity by their action of Mycobacterial ATPase. Objective: The structural features necessary for a good antitubercular activity for a series of quinoline derivatives were explored through computational chemistry tools like QSAR and combinatorial library generation. In the current study, 3-Chloro-4-(2-mercaptoquinoline-3-yl)-1-substitutedphenylazitidin-2-one derivatives have been designed and synthesized based on molecular modeling studies as anti-tubercular agents. Methods: 2D and 3D QSAR analyses were used to designed compounds having a quinoline scaffold. The synthesized compounds were evaluated against active and dormant strains of Mycobacterium tuberculosis (MTB) H37 Ra and Mycobacterium bovis BCG. The compounds were also tested for cytotoxicity against MCF-7, A549 and Panc-1 cell lines using MTT assay. The binding affinity of designed compounds was gauged by molecular docking studies. Results: Statistically significant QSAR models generated by the SA-MLR method for 2D QSAR exhibited r(2) = 0.852, q(2) = 0.811, whereas 3D QSAR with SA-kNN showed q(2) = 0.77. The synthesized compounds exhibited MIC in the range of 1.38-14.59(mu g/ml). These compounds showed some crucial interaction with MTB ATPase. Conclusion: The present study has shown some promising results which can be further explored for lead generation.
Keywords: combilib; Molecular docking; mycobacterial ATPase; QSAR; Quinoline

Novel gene similar to nitrite reductase (NO forming) plays potentially important role in the latency of tuberculosis - Agrawal, Sonia; Gample, Suwarna; Yeware, Amar; Sarkar, Dhiman (Scientific Reports, 2021)
The development of the latent phenotype of Mycobacterium tuberculosis (Mtb) in the human lungs is the major hurdle to eradicate Tuberculosis. We recently reported that exposure to nitrite (10 mM) for six days under in vitro aerobic conditions completely transforms the bacilli into a viable but non-cultivable phenotype. Herein, we show that nitrite (beyond 5 mM) treated Mtb produces nitric oxide (NO) within the cell in a dose-dependent manner. Our search for the conserved sequence of NO synthesizing enzyme in the bacterial system identified MRA2164 and MRA0854 genes, of which the former was found to be significantly up regulated after nitrite exposure. In addition, the purified recombinant MRA2164 protein shows significant nitrite dependent NO synthesizing activity. The knockdown of the MRA2164 gene at mRNA level expression resulted in a significantly reduced NO level compared to the wild type bacilli with a simultaneous return of its replicative capability. Therefore, this study first time reports that nitrite induces dormancy in Mtb cells through induced expression of the MRA2164 gene and productions of NO as a mechanism for maintaining non-replicative stage in Mtb. This observation could help to control the Tuberculosis disease, especially the latent phenotype of the bacilli.

Probes and techniques used in active and the hypoxia-based dormant state of an antitubercular drug screening assay - Yeware, Amar; Akhtar, Shamim; Sarkar, Dhiman (Medicine in Drug Discovery, 2022)
Current antitubercular drug therapy requires more than six months and is unable to kill latent or dormant forms of tuberculosis. Thus, it is a need of new drug therapy to fight against dormant tuberculosis. However, the major obstacle in the development of novel drugs for dormant tuberculosis is the lack of relevant screening systems and using reliable probes to measure growth inhibition. Until now, several probes used in active state assays are significantly determining the inhibitory effect against the active state of mycobacteria. The dormant condition assays are based on hypoxia-derived dormancy which include resazurin reduction assay, nitrite reductase assay, XTT reduction menadione assay and low oxygen recovery assay. Major probes used in those assays are colorimetric/fluorescent dyes, enzymatic activity, and reporter genes include luciferase and fluorescent proteins. Although these dormant assays are based on hypoxia-induced features and difficult to maintain for a longer duration. Also, they further complicated by growth detection and pursuit of high throughput screening criteria. Here we reviewed complications of probes and assay techniques used for anti-dormant drug screening programs of tuberculosis. This will provide the knowledge to design better alternative drug screening method for the anti-dormant form of tuberculosis.
Keywords: Active and dormant states; and; Drug screening assay; Probes; tuberculosis